The role of microphytobenthos on shallow coastal lagoons: a modelling approach - Brito, Ana (2012)
Ria Formosa is a Region of Restricted Exchange given its limited connection to coastal water circulation. Furthermore, it is subject to several anthropogenic activities that can lead to an increase in nutrients and potentially to eutrophication. Previous studies have shown the importance of the benthic compartment, specifically the microphytobenthos (MPB) in this shallow coastal lagoon. The dCSTT– MPB model [new version of the dynamic Comprehensive Studies Task Team (dCSTT) model] here described couples the benthic and pelagic compartments. Due to the shallowness of the system, the benthic microalgae are one of the most important primary producers of the system. Preliminary results of the model show a large biomass of benthic microalgae, which strongly influences the pelagic chlorophyll concentration by resuspension. However,algae concentrations in the water column are relatively small due to the high flushing rate of the lagoon. The MPB community is mainly supported by nutrients in the pore water. A sensitivity analysis (SA) has revealed that the factors associated with the benthic compartment were the most important and sensitive to changes. Porosity, benthic chlorophyll recycling, loss of MPB due to grazing and the yield of microphytobenthic chlorophyll from nitrogen were some of the most sensitive parameters, as well as the ones associated with decay of particulate organic nitrogen. The development of our dCSTT–MPB model has itself provided insights into benthic function.